Diplopia After Migraine Surgery. Issue 5 (15th July 2021) - Celik Buyuktepe, Tuna; Bingöl Kiziltunç, Pinar; Atilla, Huban
Abstract : A 46-year-old man with refractory migraine headache was treated with decompressive migraine surgery of the supraorbital and supratrochlear nerves. Postoperatively, he reported diplopia that got better on left head tilt. After ophthalmological examination, a diagnosis of right superior oblique palsy was made. The aim is to report the first case of superior oblique muscle or trochlea damage that may have occurred because of inadvertent entry through the orbital septum into the right superior orbit. Abstract : We report a novel case with diplopia due to superior oblique muscle tendon or trochlea injury after migraine surgery with supraorbital and supratrochlear nerve decompression.